If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 13 + -3x + -7 = 0 Reorder the terms: 13 + -7 + 6x + -3x = 0 Combine like terms: 13 + -7 = 6 6 + 6x + -3x = 0 Combine like terms: 6x + -3x = 3x 6 + 3x = 0 Solving 6 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = 0 + -6 3x = 0 + -6 Combine like terms: 0 + -6 = -6 3x = -6 Divide each side by '3'. x = -2 Simplifying x = -2
| 228=12x | | y=2x^2-8x-10 | | y-16+15=60 | | 36-2=-45 | | 2.8+2.2+x=0 | | 4.7+10m=6.98 | | 10x+15+13x+26x=180 | | 13x+7=39 | | 72/y-6=6 | | C=5x^2-200x+4000 | | 2+5+x=0 | | 3x^2+x=3.75 | | X^2-46x+225=0 | | 400=x^2 | | (x+15)(x+5)(10x-20)=180 | | t/5-4=13 | | 5.9x=-17.11 | | -2*(t-1)=3*(6t-6) | | (x^2+5x-7)(x^2-x+4)-(x+2)(x-3)= | | 10x^2-23=-12 | | y+7x=114 | | 4x-.2=1 | | F(x)=-2x^2-8x+2 | | -7n^2-7n-6=0 | | (3x^2+4)(2x^2-3)+4x(3x-5)= | | r-10=-9 | | 18z-2z-1=16z+2 | | 4(x-2)+2x=3x-5 | | (2x^2-3)(x^2+4)= | | -5k^2+2k-1=0 | | 2(5-4y)=10-4h | | (-1+5i)(-1-5i)=0 |